2013
DOI: 10.1111/ctr.12143
|View full text |Cite
|
Sign up to set email alerts
|

Low‐pressure pneumoperitoneum during laparoscopic donor nephrectomy to optimize live donors’ comfort

Abstract: Nowadays, laparoscopic donor nephrectomy (LDN) has become the gold standard to procure live donor kidneys. As the relationship between donor and recipient loosens, it becomes of even greater importance to optimize safety and comfort of the surgical procedure. Low-pressure pneumoperitoneum has been shown to reduce pain scores after laparoscopic cholecystectomy. Live kidney donors may also benefit from the use of low pressure during LDN. To evaluate feasibility and efficacy to reduce post-operative pain, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 8 publications
3
31
1
Order By: Relevance
“…In a previous pilot study by our group, low-pressure pneumoperitoneum (7 mmHg) during laparoscopic donor nephrectomy reduced postoperative pain scores, compared with standard pressure pneumoperitoneum [7]. This finding is in agreement with a meta-analysis showing that the use of low-pressure pneumoperitoneum provides a clinically relevant reduction in postoperative pain scores after laparoscopic surgery [8].…”
Section: Introductionsupporting
confidence: 82%
“…In a previous pilot study by our group, low-pressure pneumoperitoneum (7 mmHg) during laparoscopic donor nephrectomy reduced postoperative pain scores, compared with standard pressure pneumoperitoneum [7]. This finding is in agreement with a meta-analysis showing that the use of low-pressure pneumoperitoneum provides a clinically relevant reduction in postoperative pain scores after laparoscopic surgery [8].…”
Section: Introductionsupporting
confidence: 82%
“…8 Strategies to improve the management of the referred shoulder pain component are limited; however, a recent study by our group showed that the use of low-pressure pneumoperitoneum (7 mmHg) was feasible and significantly reduced referred shoulder pain after laparoscopic donor nephrectomy. 9 Limitations of this study are mainly related to its exploratory design without a sample size calculation, i.e. this study was not adequately powered to identify risk factors for post-operative pain in a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all of these facts, we thought that our results may be by the mechanical effect of pneumoperitoneum on intraabdominal organ and not by the irreversible impairment of liver function. Nowadays, intraabdominal pressure for induced pneumoperitoneum often is set as low as 7-8 mmHg because it guarantees advantage in postoperative complication such as overall postoperative pain, preservation of pulmonary function, or at least there are no differences postoperative outcome [22,23]. But this low pressure method has some drawbacks.…”
Section: Discussionmentioning
confidence: 99%